Twilight of the warriors : walled in [videorecording (DVD)] - Ou, Jianer; Chan, Tai Lee (Film director); Shum, Kwan Sin; Chun, Jack Lai; Gu, Tianle, 1970-; Hung, Samo, 1952-; Ren, Xianqi; Lin, Feng, 1979-; Liu, Junqian; Wu, Yunlong, 1977-; Hu, Zitong, 1992-; Zheng, Zhaoqiang; et al. (Well Go USA Entertainment, 2024)
Many years after the bloody turf war that ushered in an uneasy era of peace in Hong Kong's underworld, the notorious Kowloon Walled City serves as a fortified, lawless safe haven for gangs and refugees alike. But when a skilled underground fighter runs afoul of the most feared Triad boss in Hong Kong, a bounty is placed on his head despite his connections to the leader of the infamous enclave. As his pursuers violate the tenuous territorial truce to exact their vengeance, the fallout reignites old grudges, bringing decades of building tension to a brutal, bloody boiling point.